Pemberdayaan UMKM Kampoeng Batik Jetis Kabupaten Sidoarjo melalui Strategi Branding Pada Era Disrupsi - Aphief Tri Artanto; Arista Pratama; Sukirmiyadi Sukirmiyadi; Kusnarto Kusnarto; Endang Sholihatin Sholihatin (Journal of Governance and Administrative Reform)
Micro, small and medium enterprises (MSMEs) play an important role in economic development because of their considerable contribution to job creation and improving people's welfare. Problems that often arise in MSMEs include limited capital, lack of innovation, conventional marketing, inefficient financial management, weak branding, lack of innovation, not maximizing online marketing due to technological stuttering. This research focuses on empowering MSMEs for branding strategies in competitive batik products in order to win the market based on the concept of blue ocean strategy. This study used qualitative research methods. The research location is Kampoeng Batik Jetis, Sidoarjo Regency. Data were collected through in-depth interviews, documentation studies, and observations. The unit of research analysis is the individual level of MSME actors. This research is a descriptive qualitative research. The data analysis of this study used qualitative data analysis techniques following Miles and Huberman. Conclusion Branding strategy on batik product competition in order to be able to win the market based on the concept of blue ocean strategy by: (a) added value (b) creating and (c) enhancing features and benefits.